PERLINDUNGAN HUKUM INDIKASI GEOGRAFIS TERHADAP PRODUK MASYARAKAT ADAT DI INDONESIA : Studi Kasus Masyarakat Adat Baduy - Julia Elfany Shavira (Institut Pendidikan Tapanuli Selatan, 2021)
Geographical Indications are part of Intellectual Property Rights and are also important that can boost the reputation of a region. Indigenous peoples themselves are people who living regularly that occupies an area that has its own traditions and uniqueness that differs from region to region. Geographical indications and Indigenous Peoples themselves are very closely related to each other, where there is an similarity between the two things that are equally related to the characteristics in a region. The purpose of this study is to find out what obstacles experienced by the Baduy Indigenous Peoples in registering their distinctive products into syndicated products and what efforts or solutions can be made to minimize these barriers. Related with this research, the method used is Normative Juridical method by using statute approach and in the process of collecting data obtained through literature study and data analysis method using descriptive analytical method. The results show that indigenous peoples themselves have not made legal protection of the products produced into a need or urgency that must be immediately obtained protection. Keywords: Legal Protection, Geographical Indications, Indigenous Peoples